(untitled) (Journal of Atomic and Molecular Sciences, 2021)
Batch experiments are carried out for the sorption of cationic dyes such as crystal violet, Malachite green and Rhodamine B dyes onto corncob acid treatment. The operating variables studied are contact time and pH. Equilibrium adsorption isotherms and kinetic were investigated. The experimental data were analyzed by the Langmuir and Freundlich models and the isotherm data fitted well to the Langmuir isotherm. The kinetic data obtained were analyzed using a pseudo-first order and pseudo-second-order equation and intra particle diffusion equation. The experimental data fitted very well the pseudo-second-order kinetic model.